Andrew T. Cowart and Karl Erik Brofoss, Decisions, Politics and Change: A Study of Norwegian Urban Budgeting, Oslo: Universitetsforlaget, 1979. 1515., 55,00 Nkr - P. Kristensen, Ole (Politica, 1980)
-